Development of Moodle-Based E-Learning Media for News Writing - Firly Laila Rahma Aini; Ridho Kurniawan; Muhammad Rusli (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to develop Moodle-based e-learning media to support the teaching of news writing in Grade 7 at MTs Al-Ijtimaiyah Siluman. The development of this digital media is intended to enhance the effectiveness and engagement of students in learning news writing, a critical component of journalism education at the junior secondary level. Many students find news writing challenging due to limited resources and monotonous learning approaches. Therefore, integrating technology such as Moodle is expected to provide a more interactive and student-centered learning experience. The study adopts a development research approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. During the analysis stage, the students’ needs, existing resources, and curriculum requirements were examined. The design and development stages focused on creating structured learning content, exercises, and interactive features suitable for 7th-grade learners. The implementation stage involved testing the Moodle-based media in a classroom setting with 30 seventh-grade students at MTs Al-Ijtimaiyah Siluman. In the final evaluation stage, data were collected through observations, pre- and post-tests, and student questionnaires to measure effectiveness and user satisfaction. The results show that the developed media significantly improved students’ learning outcomes in news writing. Pre- and post-test scores indicated an average increase of 32%, demonstrating better understanding of news structure, language, and reporting techniques. In addition, over 85% of students reported that the Moodle platform made the learning process more enjoyable and easier to follow. These findings suggest that Moodle-based e-learning media is an effective tool to improve news writing skills and can be a valuable resource for teachers in delivering more engaging and effective instruction.